Moral courage level of nurses: a systematic review and meta-analysis - Hang Li; JuLan Guo; ZhiRong Ren; Dingxi Bai; Jing Yang; Wei Wang; Han Fu; Qing Yang; Chaoming Hou; Jing Gao (BMC, 2024)
Abstract Background Moral distress occurs in daily nursing work and plagues nurses. Improving the level of moral courage is one of the main strategies to reduce moral distress, and low levels of moral courage may lead to nurse burnout, increased turnover, and reduced quality of care. Methods Nine electronic databases in Chinese and English were searched for the level of moral courage among nurses, including PubMed, Web of Science, EMBASE, CINAHL, CNKI, Wan fang, Wei pu, CBM and Cochrane Library, for the period from the date of database creation to April 5, 2023. The Agency for Healthcare Research and Quality (AHRQ) was used to assess the methodological quality of the included studies, followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and the Meta-analysis and Systematic Reviews of Observational Studies guidelines, and data from the included studies were meta-analyzed in STATA version 15 using a fixed-effects model. Results Seventeen cross-sectional studies of moderate or high quality met the eligibility criteria and involved 7718 nurses, and the Nurses' Moral Courage Scale (NMCS) was used to measure the self-assessed moral courage level of nurses. Eleven of these studies reported total scores for nurses' moral courage, and the meta-analysis results showed a pooled mean score of 78.94 (95% CI: 72.17, 85.72); Fourteen studies reported mean entry scores for nurses' moral courage, and the meta-analysis results showed a pooled mean score of 3.93 (95% CI: 3.64, 4.23). Conclusion The results of the meta-analysis showed that nurses' moral courage levels were in the medium to high range, among the nurses who seemed to be male, non-nursing managers, high school education, had not experienced ethical issues, and considering resignation had lower levels of moral courage. The results of the meta-analysis may provide some reference for nursing managers and even hospital administrators to develop strategies to optimize nursing quality.